Effect of Duck Egg Shell Ash with Fly Ash as Cement Substitution in Geopolymer Concrete - Larasati, Deka; Nurtanto, Dwi; Utami, Nanin Meyfa (BERKALA SAINSTEK, 2022)
The increasing production of cement as a basic material for making concrete is due to the increasing demand for concrete throughout the world. Innovative materials are needed as a substitute for cement to reduce the greenhouse effect, fly ash is pozzolanic which in fact has the potential to replace Portland cement as the main ingredient of concrete, and duck eggshell flour has good prospects to be used as an additional precursor material for geopolymer concrete. This study aims to determine further variations of the proportion of duck egg shells, the mechanical properties of the concrete produced using duck egg shell ash with fly ash. This study used an experimental method with the percentage of duck egg shell ash at 0%, 5%, 10%, and 15% of the total use of cement. Using Na₂SiO₃ and NaOH as activator with a concentration of 14M. At the age of 7 and 28 days with room temperature treatment. This study resulted in duck egg shell ash being able to increase the compressive strength of concrete at the age of 28 days with the percentage of substitution up to 5% with a value of 59.26 MPa, in the porosity test the minimum value was at the age of 28 days at a percentage of 5% 0.403%, and the value of the modulus of elasticity. experienced an increase in value at a percentage of 5% with the result 36071.43 MPa. Duck egg shell ash with a proportion of 5% is the optimum substitution where the compressive strength, porosity and modulus of elasticity tests on geopolymer concrete have linear values.